Eastern comma, hop merchant, comma angelwing, Polygonia comma (Harris) (Insecta: Lepidoptera: Nymphalidae: Nymphalinae) - Donald W. Hall; Jerry F. Butler (EDIS)
EENY455, a 4-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this small inconspicuous butterfly that prefers moist woods — its distribution, description, life cycle and biology, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.